Review of specialized degree-granting graduate programs of the Department of Defense in STEM and Management (The National Academies Press, 2014)
The United States military is arguably the most intensely technological, complex enterprise in existence. When compared to the gross domestic products of other countries, the Department of Defense (DoD) budget ranks above all but about 20 nations. If viewed as a company, it would be the largest globally with the most employees. Major investments in weapons systems using advanced technologies provide an advantage over competing systems. Each weapon, platform, vehicle, and person in an operating force is a node in one or more advanced networks that provide the ability to rapidly form a coherent force from a large number of broadly distributed elements. DoD's ability to create and operate forces of this nature demands a competent understanding by its workforce of the composition, acquisition, and employment of its technology-enabled forces. Review of Specialized Degree-Granting Graduate Programs of the Department of Defense in STEM and Management focuses on the graduate science, technology, engineering, mathematics and management (STEM+M) education issues of the Air Force, Navy, and Marines. This report assesses the cost, benefits, and organizational placement of DoD institutions that grant degrees in STEM+M and evaluates alternative ways - for example, civilian institutions and distance learning - to ensure adequate numbers and high-quality education outcomes for DoD personnel."--Publisher's description